A review on PFAS mitigation in wastewater: integrating removal technologies, challenges and innovative solutions - Ilenia Farina; Antonella Scotto di Uccio; Alessandro Moretti; Francesco Colangelo (Reviews in Environmental Science and Bio/Technology, 2026)

Around the world in eight white rot species: Assessment of enzymatic and non-enzymatic wood decay pathways of worldwide Esca Complex of Diseases (ECD) associated basidiomycetes - Alessandro Puca; Samuele Moretti; Mary-Lorène Goddard; Jacques Lalevée; Hanns-Heinz Kassemeyer; Sibylle Farine; Laura Mugnai; Christophe Bertsch (Fungal Biology, 2025)

The role of grey water footprint in urban wastewater management: from pollution to reuse - Andrea Zanolla; Alessandro Moretti; Daniele Goi (Environmental Science and Pollution Research, 2025)

Extracellular polymeric substances (EPS) in sewage sludge management: A call for methodological standardization - Hajer Ben Hamed; Matia Mainardis; Alessandro Moretti; Dominique Toye; Angélique Léonard (Journal of Environmental Management, 2025)

Integrating renewable energy in sewage sludge treatment through greenhouse solar drying: A review - Marlee Wasserman; Alessandro Moretti; Daniele Goi; Matia Mainardis (Science of The Total Environment, 2025)

EU2030 biodiversity strategy: Unveiling gaps in the coverage of ecoregions and threatened species within the strictly protected areas of Italy - Roberto Cazzolla Gatti; Jacopo Iaria; Gloria Moretti; Valerio Amendola; Francesca Maura Cassola; Pierfilippo Cerretti; Michele Di Musciano; Luana Francesconi; Anna Rita Frattaroli; Martina Livornese; Matilde Martini; Dario Nania; et al. (Journal for Nature Conservation, 2024)

A review of the state-of-the-art wastewater quality characterization and measurement technologies. Is the shift to real-time monitoring nowadays feasible? - Alessandro Moretti; Heidi Lynn Ivan; Jan Skvaril (Journal of Water Process Engineering, 2024)

First evidence of widespread positivity to anticoagulant rodenticides in grey wolves (Canis lupus) - Carmela Musto; Jacopo Cerri; Dario Capizzi; Maria Cristina Fontana; Silva Rubini; Giuseppe Merialdi; Duccio Berzi; Francesca Ciuti; Annalisa Santi; Arianna Rossi; Filippo Barsi; Luca Gelmini; et al. (Science of The Total Environment, 2024)

Tackling climate change through wastewater reuse in agriculture: A prioritization methodology - Luca Penserini; Alessandro Moretti; Matia Mainardis; Beatrice Cantoni; Manuela Antonelli (Science of The Total Environment, 2024)

Sustainable thinking toward to industry's future combined with new knowledge on greenhouse effect mitigation generated by the grinding process - José Claudio Lopes; Guilherme Antonio de Carvalho; Guilherme Bressan Moretti; Benício Nacif Ávila; Matheus de Souza Rodrigues; Mateus Vinícius Garcia; Fernando Sabino Fonteque Ribeiro; Alessandro Roger Rodrigues; Luiz Eduardo de Angelo Sanchez; Eduardo Carlos Bianchi (Journal of Cleaner Production, 2023)

Emission estimates and air quality simulation on Lombardy during lockdown - Alessandro Marongiu; Elisabetta Angelino; Giulia Malvestiti; Marco Moretti; Giuseppe Fossati; Edoardo Peroni (Air Quality, Atmosphere & Health, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

First 13C/12C isotopic characterisation of volcanic plume CO2 - Giovanni Chiodini; Stefano Caliro; Alessandro Aiuppa; Rosario Avino; Domenico Granieri; Roberto Moretti; Francesco Parello (Bulletin of Volcanology, 2011)

Evaluation of ‘di Romagna’ and ‘Frenchgrey’ shallots for quality characters connected to bulb colourand volatile oil content and composition - L. Filippo D'Antuono; Alessandro Moretti; Roberta Neri (Genetic Resources and Crop Evolution, 2002)